2013
DOI: 10.1002/ijc.28471
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TIP30 expression predicts poor prognosis in pancreatic cancer patients

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is known for its aggressive growth, and is characterized by early tissue invasion and metastasis with poor prognosis. Identifying prognostic markers and delineating the underlying mechanisms that promote progression of PDAC are important for the treatment of pancreatic cancer. TIP30, a newly identified tumor suppressor, appears to be involved in multiple processes during tumor development and metastasis. Here, we investigated the expression of TIP30 in PDAC and its progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…TIP30 is involved in the control of cell apoptosis, growth, metastasis, angiogenesis, DNA repair, and tumor cell metabolism [11]. TIP30 has been found to be expressed in a wide variety of tumor tissues, including esophageal carcinoma [12], laryngeal carcinoma [13], glioma [14], pancreatic ductal adenocarcinoma [15], breast cancer [16], gastric cancer [17], gallbladder adenocarcinoma [18], lung cancer [19], and hepatocellular carcinoma [20]. The methylation of the TIP30 promoter may also be associated with tumor prognosis [21], but there are conflicting results from another study [22].…”
Section: Introductionmentioning
confidence: 99%
“…TIP30 is involved in the control of cell apoptosis, growth, metastasis, angiogenesis, DNA repair, and tumor cell metabolism [11]. TIP30 has been found to be expressed in a wide variety of tumor tissues, including esophageal carcinoma [12], laryngeal carcinoma [13], glioma [14], pancreatic ductal adenocarcinoma [15], breast cancer [16], gastric cancer [17], gallbladder adenocarcinoma [18], lung cancer [19], and hepatocellular carcinoma [20]. The methylation of the TIP30 promoter may also be associated with tumor prognosis [21], but there are conflicting results from another study [22].…”
Section: Introductionmentioning
confidence: 99%
“…TIP30 is an important prognostic predictor for various cancers. 19, 48, 49 Upregulated SREBP1 associated with a poor prognosis of HCC patients. 50 Remarkably, when the combined effects of TIP30 and SREBP1 were evaluated, the sensitivity for survival analysis of HCC patients was improved.…”
Section: Discussionmentioning
confidence: 98%
“…12, 13, 14, 15, 16, 17, 18 Moreover, we also found downregulated TIP30 induces epithelial–mesenchymal transition in HCC and pancreatic cancer. 19, 20 …”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors have been identified as essential in oligodendrocyte development (Li et al, ; Wegner, ), such as Olig1 and Olig2, which play essential roles in oligodendrocyte specification and maturation (Lu et al, ; Takebayashi et al, ; Zhou et al, ). In this study, we have defined a crucial role for TIP30, a cytosolic protein that has been correlated with tumorigenesis and tumor metastasis (Guo et al, ; Kumtepe et al, ; Li et al, ; Tong et al, ), in regulating OL differentiation. We found that TIP30 was expressed in all oligodendrocyte lineage stages and was significantly down‐regulated from 2–3 weeks postnatal, a period critical for myelin formation (Chen et al, ), suggesting that it may serve as an OPC differentiation inhibitor.…”
Section: Discussionmentioning
confidence: 98%